Paleomagnetic studies of intrusives in the deccan trap around Nandurbar Area, South of Tapti Valley,District Dhule, Maharashtra - Sethna, S. F.; Khateeb, Ateeq; Rao, D. R. K.; Saraf, P. D. (My University, 1999)
The area around Nandurbar consists of compound lava flows (basalts) of Deccan Trap which are intruded by numerous prominent dykes. These dykes are mainly dolerites and some are quite massive and extensive. One major dyke wastraced for over 50 km, from north of Dondaicha, westwards as far as Umaj, near the Gujarat - Maharashtra border. Petrochemical studies indicate tholeiitic nature of the magma. There is also an indication of two distinct magma types represented by high Ti and low Ti varieties. These two magma types have intruded as distinct phases with the high Ti dykes being cut across bythe low Ti dykes. The palaeomagnetic work centers around these dykes. In addition a few lavaflows were studied for comparison. The older set of dykes show normal magnetization whilst the younger set shows reverse directions. The lava flows are also reversely magnetized. It is thus evident that both the dyke phases ale younger than the surrounding lava flows. The older phase of dykes couldhave been feeders to the younger lava flows of the Deccan Volcanic Province but the younger phase is distinctly post Deccan Trap.
Keywords: Palaeomagnetism; Maharashtra; Tapti valley; Dykes; Deccan Trap